2016
DOI: 10.3945/jn.115.223990
|View full text |Cite
|
Sign up to set email alerts
|

The Colonic Microbiome and Epithelial Transcriptome Are Altered in Rats Fed a High-Protein Diet Compared with a Normal-Protein Diet

Abstract: Our findings suggest that the HPD altered the colonic microbial community, shifted the metabolic profile, and affected the host response in the colons of rats toward an increased risk of colonic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 46 publications
8
92
1
1
Order By: Relevance
“…Such an increase in Lactobacillus and lower abundance of Bifidobacteria was found consistently in the ileum and in the cecum. Interestingly, high‐protein diet in humans, pigs and rats also decreased Bifidobacteria and/or increased Lactobacillus abundances . Therefore, LFE diet seems to replicate some of the effects of high‐protein diets, which are related to a greater peptides supply in the distal part of the gut.…”
Section: Discussionmentioning
confidence: 96%
“…Such an increase in Lactobacillus and lower abundance of Bifidobacteria was found consistently in the ileum and in the cecum. Interestingly, high‐protein diet in humans, pigs and rats also decreased Bifidobacteria and/or increased Lactobacillus abundances . Therefore, LFE diet seems to replicate some of the effects of high‐protein diets, which are related to a greater peptides supply in the distal part of the gut.…”
Section: Discussionmentioning
confidence: 96%
“…Of note, the microbiota has been proposed to play an important role in regulating host energy homeostasis through oxidative phosphorylation (49). Furthermore, a recent mouse study showed that alterations in diet can alter colonic microbial composition as well as downregulation of oxidative phosphorylation genes (50). Further investigation is needed to reveal the mechanistic insight between Paneth cell function, microbiota changes, and oxidative phosphorylation status in the context of CD.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies showed that a modification of the protein intake alters the composition of the gut microbiota despite important variations, according to the experimental design. Interestingly, two studies performed with rats receiving an HP diet reported a significant decrease in the abundance of Faecalibacterium prausnitzii in the large intestine [22,23]. This commensal bacterium has demonstrated anti-inflammatory properties in vivo using a mouse colitis model.…”
Section: Potential Influence Of Dietary Proteins On Inflammatory Bmentioning
confidence: 99%